PENGARUH LIKUIDITAS, SOLVABILITAS DAN AKTIVITAS TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR SUB SEKTOR PLASTIK DAN KEMASAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2018 - Eka, Dede (Politeknik Negeri Lhokseumawe, 2025)
Abstract: This study aims to determine and analyze the effect of liquidity, solvency, and activity on company profitability. The research method used is descriptive and verification methods. The study population is the plastic and packaging sub-sector manufacturing companies listed on the Indonesian Stock Exchange for the period 2014-2018. The sample used is 11 plastic and packaging sub-sector manufacturing companies through a purposive sampling method while the data uses secondary data from financial reports for the period 2014-2018. The data analysis technique used is Panel Data Regression Analysis using the Eviews application. The results of the study indicate that Liquidity, Solvency, and Activity together affect profitability. Liquidity has a positive and significant effect on profitability. This is a finding that a company's ability to pay off short-term liabilities well can increase the increase in returns on capital, especially the company's internal capital. Solvency has a positive and significant effect on profitability. This is a finding that a company's ability to pay off long-term liabilities well can affect the rate of return on capital, especially the company's internal capital. Activities have a positive and significant influence on profitability. This is a finding that the company's effectiveness in managing inventory turnover into good sales can affect the level of profit or return on capital, especially the company's internal capital.Keywords: Profitability, Liquidity, Solvency, Activity.